Co-inoculação, osmoproteção e aplicação de cobalto e molibdênio na cultura da soja - Stecca, Jessica Deolinda Leivas (2020)
Crop productivity is strongly related to plant nutrition. In soybean, nitrogen (N) is the nutrient required in greater quantity, being involved in growth and development processes of the crop. In Brazil, the availability of N for soybeans occurs through biological nitrogen fixation (FBN), which depends on the inoculation process with bacteria. However, the efficiency of the process is subject to several factors such as seed treatment (TS), which can reduce the survival of inoculated bacteria, and availability of nutrients. In this context, the objective was to evaluate the use of an osmoprotector between co-inoculation and the application of Cobalt (Co) and Molybdenum (Mo) via TS, and its effects on nodulation, yield components, protein content in the grains, enzymatic changes in plants and the quality of next generation soybean seeds. Experiments were conducted with the cultivars NS 5959 IPRO and TMG 7062 INTACTA. The experimental design involved a bifactorial (2 x 3) + 1, with four and three repetitions, consisting of using or not the osmoprotector; application of Co and Mo in the seeds, leaf or without application; and additional control (seeds with fungicide and insecticide). In chapter I, the performance of plants in the field and the protein content of the grains were evaluated. In chapter II with the leaves from the plants of the field experiment, the enzymatic changes were evaluated and, from the seeds, their quality was evaluatedIn chapter III, the analysis of canonical correlations between the characters of the plant (mass and number of nodules, dry mass of aerial part, number of pods, mass of a thousand grains and grain yield) and seed (length of aerial part and root, seedling dry mass, accelerated aging, electrical conductivity, first count and germination); physiological variables (protein content in the grain and leaf, carotenoids and activity of the guaiacol peroxidase enzyme) and the group of plant variables; and physiological and seed; and within each character group the Pearson linear correlation. The main results obtained were: the osmoprotector together with the chemical treatment of seeds reduces the dry mass of nodules, mass of a thousand grains, number of pods and grain yield (PG); annual seed co-inoculation promotes increases in PG and maintains the physiological quality of the harvested seeds; co-inoculation increases the protein content of leaves and grains; the use of co-inoculation associated with Co and Mo increase PG; the analysis of canonical correlations shows that the groups of variables of plant, seed and physiological are not independent, defining the characteristics that should be prioritized in the evaluations, being dependent on the evaluated cultivar. Thus, it is concluded that the co-inoculation associated with the application of Co and Mo is a technology that contributes to the increase in grain productivity, in the quality of next generation seeds and in the protein content of the soybean grain, without cause environmental damage and relatively low production cost.